Vascular Calcification in Patients with Large-Vessel Vasculitis Compared to Patients with Hyperlipidemia - Banerjee, Shubhasree (Semin Arthritis Rheum, 2018)
OBJECTIVE: Calcification of the coronary arteries, aorta, and branch vessels can occur in both large-vessel vasculitis (LVV) and atherosclerosis. The study objective was to determine the location and amount of vascular calcification in patients with LVV versus hyperlipidemia (HLD) and to identify risk factors associated with vascular calcification in LVV. METHODS: Patients with giant cell arteritis (GCA), Takayasu’s arteritis (TAK), and HLD underwent non-contrast computed tomography of the aorta and branch vessels. Vascular calcification in 14 specific arterial territories (4 segments of the aorta, 9 branch arteries, and the coronary arteries) was quantified throughout the large arteries by a cumulative Agatston score. Multivariate linear regression analyses were used to identify associations between traditional and disease-specific risk factors and total Agatston score. RESULTS: A total of 88 subjects, including GCA (n=29); TAK (n=22); and HLD (n=37), participated.Prevalence of vascular calcification in the aorta and branch vessels significantly differed in the coronary arteries (HLD=67%, GCA=35%, TAK=9%, p<0.01). Total Agatston scores were higher in GCA (median 3260, range 25-18138) versus HLD (460, 19-17215) (p<0.01) but did not significantly differ between GCA and TAK (1944, 52-47520) (p=0.53). In multivariable regression analysis, age, type of vasculitis, and prednisone use was associated with vascular calcification in LVV. CONCLUSION: The prevalence of coronary artery calcification is lower in LVV compared to HLD, but the amount of total vascular calcification throughout the large arteries is greater in LVV. Both traditional and disease-specific risk factors are associated with vascular calcification in LVV.